Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Minat Belajar Siswa Tunagrahita Kelas Viii Slb Bina Karya Insani Karanganyar Tahun Ajaran 2016/2017 - Mustafa, Sholekah Ika, Drs. Muhammad Yusron, M.Ag (2017)
Education is the main need for every man, as well as handicapped children. Education for handicapped (mental retardation) requires particular approaches and learning processes has caused intelligentsia under average.The role of Islamic religious education teachers is very important in increasing interest in studying the implementation of learning and religious values seeding. In addition teachers must also perform special approaches in order to achieve the goal. Especially regarding the student's interest in mental retardation that often fluctuate very influential towards students success in learning.Therefore, a teacher in the face of lack of interest or concern to receive the lesson then as much as possible to be able to generate interest lobbies for student learning by developing all the potential. From the background then arise problems how the formulation on the role of Islamic education teachers in increasing student interest in studying mental retardation and whatever factor endowments and Islamic religious education teachers a barrier in improving student learning interest in mental retardation. This research aims to know the role of teacher of Islamic education in improving student learning interest in mental retardation. According to the type of this research is the kind of field research. As for the study indicated to the SLB Bina Insani Karanganyar Works. The research approach used is descriptive qualitative. The subjects in this study was the teacher of Islamic education and students of class VIII of mental retardation. Methods of data collection are needed in this study i.e., interviews, documentation, observation and data analysis. Based on the results of research on the role of Islamic education teachers in increasing student interest in studying mental retardation class VIII include: the role of Teacher Education as a teacher of Islam, Islamic religious education teachers as mentors and teachers of Islamic religious education as a motivator. Factors that hinder the process of teaching and learning of students mental retardation is when children feel lazy, tired and unwilling to learn. Factors that support the teaching and learning process of the student's mental retardation is when the child focus want to work together to study and have a high learning interest.